2018
DOI: 10.1016/j.ajoc.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Removal of choroidal neovascular membrane in a case of macular hole after anti-VEGF therapy for age-related macular degeneration

Abstract: PurposeThe formation of macular hole after receiving anti-vascular endothelial growth factor (anti-VEGF) therapy is rare. We report a case of macular hole that occurred after intravitreal injection of an anti-VEGF agent for age-related macular degeneration (AMD) in a patient, who underwent vitrectomy combined with choroidal neovascularization (CNV) removal.ObservationsA 64-year-old female with AMD affecting her right eye received an intravitreal injection of an anti-VEGF agent. After treatment, we identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…3 B and C). 6 The surgery was completed by performing fluid-air exchange in the vitreous cavity and then replacing with silicone oil. The patient was instructed to maintain a prone position for three days.…”
Section: Case Reportmentioning
confidence: 99%
“…3 B and C). 6 The surgery was completed by performing fluid-air exchange in the vitreous cavity and then replacing with silicone oil. The patient was instructed to maintain a prone position for three days.…”
Section: Case Reportmentioning
confidence: 99%
“…More recently, Hirata et al reported the removal of a CNV-membrane with 25-gauge instruments through the coincident presence of a macular hole after anti-VEGF therapy for AMD and observed a rapid resolution of the intraretinal macular oedema with a fast anatomical and functional recovery to 20/40. 16 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several pathogenic mechanisms have been involved in the formation of MH in AMD [4][5][6][7][8]:…”
Section: Discussionmentioning
confidence: 99%